Epidemiological profile of pediatric maxillofacial trauma: a 20-year retrospective study of patients treated by a university graduate service in Araçatuba, Brazil (Research, Society and Development, 2020)
The objective of this study is to present a 20-year retrospective analysis of cases of pediatric patients affected by facial trauma, attended by the team of Oral and Maxillofacial Surgery and Traumatology of the School of Dentistry of Araçatuba (UNESP), Brazil, and to show the incidence of these types of trauma , as well as the most common etiological factors, age and sex of pediatric patients who suffered some type of fracture and show how the social and cultural characteristics of the papulation directly alter the epidemiology of these diseases in a given region. For this purpose, a retrospective survey was carried out on the medical records of patients up to 12 years of age, according to the eligibility criteria adopted by the study, over a period of 20 years. The chi-square test was used to compare groups and Pearson's correlation to verify the association between variables. Of the 312 medical records analyzed, facial fractures were recorded in 263 (84%), which shows a high incidence of fractures in the study population, the majority of which occurred in males and the main source of trauma was related to high impact, such as traffic accidents, which caused the prevalence of fractures in the middle third of the face. Thus, it is possible to conclude that child morbidity and mortality due to maxillofacial trauma was high in our study, but it is worth mentioning that these numbers can be reduced with education and traffic safety measures, both for children and adults, who are truly responsible for this series.